Human Plague in the Southwestern United States, 1957–2004: Spatial Models of Elevated Risk of Human Exposure to Yersinia pestis. Issue 3 (28th October 2014) - Eisen, Rebecca J.; Enscore, Russell E.; Biggerstaff, Brad J.; Reynolds, Pamela J.; Ettestad, Paul; Brown, Ted; Pape, John; Tanda, Dale; Levy, Craig E.; Engelthaler, David M.; Cheek, James; Bueno, Rudy; et al.
Abstract : Plague is a rare but highly virulent flea-borne zoonotic disease caused by the Gram-negative bacterium Yersinia pestis Yersin. Identifying areas at high risk of human exposure to the etiological agent of plague could provide a useful tool for targeting limited public health resources and reduce the likelihood of misdiagnosis by raising awareness of the disease. We created logistic regression models to identify landscape features associated with areas where humans have acquired plague from 1957 to 2004 in the four-corners region of the United States (Arizona, Colorado, New Mexico, and Utah), and we extrapolated those models within a geographical information system to predict where plague cases are likely to occur within the southwestern United States disease focus. The probability of an area being classified as high-risk plague habitat increased with elevation up to ≈2, 300 m and declined as elevation increased thereafter, and declined with distance from key habitat types (e.g., southern Rocky Mountain piñon—juniper [ Pinus edulis Engelm. and Juniperus spp.], Colorado plateau piñon-juniper woodland, Rocky Mountain ponderosa pine ( Pinus ponderosa P.& C. Lawson var. scopulorum), and southern Rocky Mountain juniper woodland and savanna). The overall accuracy of the model was >82%. Our most conservative model predicted that 14.4% of the four-corners region represented a high risk of peridomestic exposure to Y. pestis .